Cardiovascular Risk, Inflammation and Physical Activity in Rheumatoid Arthritis - Tierney, Marie; Fraser, Alexander; Kennedy, Norelee (Current Rheumatology Reviews, 2012)
Individuals with Rheumatoid Arthritis (RA) have increased mortality when compared with the general population. Much of this increased mortality can be attributed to cardiovascular causes. The exact cause for this increased risk has not been fully determined, although some potential mechanisms have been postulated. This overview aims to outline and discuss some of the potential factors which relate to this increased cardiovascular disease risk in the RA population. Inflammation is one such potential factor as inflammation has been shown to play a central role in all phases of atherosclerosis. Therefore, assessment of inflammatory markers may help identify those at high risk of future cardiovascular events. This paper aims to provide a deeper understanding of the links between inflammation and atherosclerosis and cardiovascular disease. Physical activity is associated with improvements in cardiovascular health in many populations. A link between inflammatory marker levels and physical activity has been determined and the literature specifically assessing this link is analysed in this overview. Although the literature is scarce regarding the RA population, two studies which investigate the relationship in this population are presented and discussed.
Keywords: Inflammatory Markers